Relaxed potential energy surface (PES) scan of adenosine 5'-diphosphate - Терентьєва, Юлія (My University, 2026)
Relaxed potential energy surface (PES) scan  of adenosine 5’-diphosphate This dataset contains quantum chemical calculation files for relaxed potential energy surface (PES) scans of the adenosine 5’-diphosphate (ADP) molecule. Ground-state geometry calculations were performed at the DFT/B3LYP/6-311+G(d,p) level of theory. The scan tracks the molecular geometry at fixed values of the C-N-C-O dihedral angle between the adenine ring and the ribose unit (evaluated in 5° increments), while allowing the phosphate groups to freely optimize into their preferred spatial orientations. All quantum chemical calculations were performed using the Gaussian 16 software package [1]. Initial molecular structures were built using the Avogadro molecular editor [2]. Acknowledgments: The authors acknowledge the Center for Collective Use of Equipment of the SCIT Supercomputer Complex of the National Academy of Sciences of Ukraine, hosted by the V.M. Glushkov Institute of Cybernetics of the National Academy of Sciences of Ukraine.